2011
DOI: 10.1002/adem.201000334
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering of a Zr‐Based Metallic Glass

Abstract: Amorphous metallic alloys are among the most recent class of metallic materials. [1][2][3] Indeed, low glass forming ability (GFA) of major alloys induces manufacturing into thin ribbons shape (thickness < 100 mm) since the 1960s. The development of bulk parts with reasonable dimensions is more recent (early 1990s), and it still concerns small variety of alloys having high GFA. The formation of metallic glasses (MGs) is kinetically controlled and obeys empirical rules first stated by Inoue. [4] Many metals can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…These amorphous materials are most often obtained by mechanical alloying, melt-spinning or atomization. Recently, Nowak et al (Nowak et al, 2011) and Perriere et al (Perriere et al, 2011) studied the phenomenon during SPS treatment at the origin of the microstructure and densification of glasses. The devitrification in metallic glasses during SPS treatment has also been studied in order to obtain composite materials or glass-ceramics (Li et al, 2010).…”
Section: State Of the Art Of The Materials Investigatedmentioning
confidence: 99%
See 1 more Smart Citation
“…These amorphous materials are most often obtained by mechanical alloying, melt-spinning or atomization. Recently, Nowak et al (Nowak et al, 2011) and Perriere et al (Perriere et al, 2011) studied the phenomenon during SPS treatment at the origin of the microstructure and densification of glasses. The devitrification in metallic glasses during SPS treatment has also been studied in order to obtain composite materials or glass-ceramics (Li et al, 2010).…”
Section: State Of the Art Of The Materials Investigatedmentioning
confidence: 99%
“…This suggests that the first mechanism described above, i.e achieving full density prior to any significant crystallization should be favored. However, in the specific case of metallic glasses, it is reported that concurrent mechanisms are involved during SPS treatment (Perriere et al, 2011).…”
mentioning
confidence: 99%
“…This is confirmed by Perriere et al . who suggest that: 1Iapplied=1idie+1ipowder considering an equivalent electrical outline of the SPS apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…From the reported experimental results, it can be assumed that the fine-grained structure of the composite was due to a sequence of several solid state reactions occurring in the reactant mixture. Flexible control over the SPS parameters allows inducing nanocrystallization of amorphous metallic [34,35] and nonmetallic [36] matrices and maintaining the nanostructure of the composite materials until the end of sintering. A further If refractory compounds are synthesized in the SPS form by exothermic chemical reactions, local heat evolution in the reaction initiation zones and the concomitant temperature rise in the adjacent regions can make it very challenging to synthesize materials with nanosized grains.…”
Section: Successful Syntheses Of Nanostructured Materials and Nanocommentioning
confidence: 99%